Prognostic Value of lncRNA DRAIC and miR-3940-3p in Lung Adenocarcinoma and Their Effect on Lung Adenocarcinoma Cell Progression - Liu Z (Dove Medical Press, 2021)
Zhenghua Liu, Shize Yang, Siyu Zhou, Shiyao Dong, Jiang Du Department of Thoracic Surgery, The First Affiliated Hospital of China Medical University, Shenyang, 110001, Liaoning Province, People’s Republic of ChinaCorrespondence: Jiang DuDepartment of Thoracic Surgery, The First Affiliated Hospital of China Medical University, No. 155 North Nanjing Street, Heping District, Shenyang, Liaoning Province, People’s Republic of ChinaTel/Fax +86-24-961200Email dujiang02116@163.comPurpose: Lung adenocarcinoma (LUAD) is a most common malignant tumor, even worse for diseases with relatively poor prognosis. Non-coding RNAs have the potential to be biomarkers for the prognosis of various cancers. LncRNA DRAIC and miR-3940-3p have been screened as dysregulated RNAs in LUAD. The clinical significance and biological function of lncRNA DRAIC and miR-3940-3p in LUAD were assessed in this study.Patients and Methods: A total of 122 cases of LUAD patients with complete clinical information were enrolled. The expression levels of lncRNA DRAIC and miR-3940-3p were determined via RT-qPCR in LUAD tissues and cells. The relationship between lncRNA DRAIC or miR-3940-3p expression and the clinicopathological features of patients was analyzed based on the Pearson Chi-square test. For the prognostic value, the Kaplan–Meier plot and multi-variate Cox proportional regression analysis were introduced. Finally, the effect of lnc DRAIC and miR-3940-3p on the LUAD cellular function was investigated by CCK-8 and Transwell assay.Results: lnc DRAIC was upregulated in LUAD tissues and cells, but miR-3940-3p was downregulated. Both of them showed significant associations with and TNM stage, lymph node metastasis, and a poor prognosis. Lnc-DRAIC and miR-3940-3p have the potential as independent prognostic factors for LUAD. Furthermore, the inhibition of lnc DRAIC can inhibit cell proliferation, migration, and invasion of LUAD partly as a ceRNA of miR-3940-3p.Conclusion: lncRNA DRAIC/miR-3940-3p axis may be involved in the progression of LUAD and can be developed to promising prognostic factors, which may provide new insights into the treatment of LUAD.Keywords: lung adenocarcinoma, lncRNA DRAIC, miR-3940-3p, progression, prognosis